2009
DOI: 10.1016/j.bbadis.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory expression of human N-Acetylglucosaminyl-1-phosphotransferase subunits in mucolipidosis type III gamma

Abstract: The N-Acetylglucosaminyl-1-phosphotransferase plays a key role in the generation of mannose 6-phosphate (M6P) recognition markersessential for efficient transport of lysosomal hydrolases to lysosomes. The phosphotransferase is composed of six subunits (alpha2, beta2, gamma2). The alpha- and beta-subunits are catalytically active and encoded by a single gene, GNPTAB, whereas the gamma-subunit encoded by GNPTG is proposed to recognize conformational structures common to lysosomal enzymes. Defects in GNPTG cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…These data indicate that loss of the γ subunit does not reduce phosphotransferase activity towards a simple sugar substrate. Further, RT-PCR analyses of gnptg −/− embryos showed normal levels of gnptab mRNA, suggesting that the γ subunit does not influence αβ expression in this system, in contrast to what has been noted in cells (26,27). …”
Section: Resultsmentioning
confidence: 56%
“…These data indicate that loss of the γ subunit does not reduce phosphotransferase activity towards a simple sugar substrate. Further, RT-PCR analyses of gnptg −/− embryos showed normal levels of gnptab mRNA, suggesting that the γ subunit does not influence αβ expression in this system, in contrast to what has been noted in cells (26,27). …”
Section: Resultsmentioning
confidence: 56%
“…Furthermore, quantitative real-time PCR showed that the relative mRNA level of both GNPTAB and GNPTG were elevated to a similar extent compared with those in human fibroblasts or Hela cells (Table 1), indicating the stability of mRNAs. In contrast, a characteristic finding in fibroblasts of MLIII patients exhibiting mutations in GNPTG gene, is the compensatory increase in GNPTAB mRNA expression (11,24), which was not observed in macrophages. These data support the idea that neither genomic nor transcriptional alterations in GNPTAB/GNPTG are responsible for the loss in GlcNAc-1-phosphotransferase activity in macrophages.…”
Section: Discussionmentioning
confidence: 69%
“…The construct was sequenced on an ABI PRISM 377 DNA Sequencer (University Medical Center Service Laboratory, Hamburg-Eppendorf). The expression vector coding for the N-terminally Myc-tagged ␥-subunit has been described elsewhere (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UDP-GlcNAc phosphotransferase, which has an ␣ 2 ␤ 2 ␥ 2 subunit structure, catalyzes the initial step in the mannose-6-phosphate modification of lysosomal hydrolases that is necessary for targeting these proteins to the lysosome. The ␣ and ␤ subunits are encoded by a single gene and are thought to contain the catalytic portion of the protein (39), whereas the ␥ subunit is encoded by a separate gene and is thought be a regulatory element (40,41). Based on our studies, Xpt1p cannot utilize FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%